The rediscovery of the rare Vietnamese endemic Eriophorum scabriculme redefines generic limits in the Scirpo-Caricoid Clade (Cyperaceae) - Starr,Julian R.; Léveillé-Bourret,Étienne; Tài,Vũ Anh; Thị Kim Thanh,Nguyê˜n; Ford,Bruce A. (PeerJ, 2019)
For those familiar with boreal bogs and wet tundra, species of Eriophorum (“the cotton grasses”) will undoubtedly represent some of the most striking and memorable taxa they have encountered. This small genus of 20 Holarctic sedge species (Cyperaceae) is remarkable because its inflorescences produce large, brilliantly white to rusty-red cottony masses when its flowers develop a perianth of highly elongated bristles after anthesis. In this study, we document the rediscovery of Eriophorum scabriculme, a narrow Vietnamese endemic known from only two collections made approximately 7 km apart near Sa Pa in Lào Cai Province over 75 years ago. Using plastid DNA sequences (matK, ndhF), embryology, and morphology, we test whether E. scabriculme is aligned within the Scirpo-Caricoid Clade (genus Khaosokia and tribes Cariceae, Dulichieae, Scirpeae, and Sumatroscirpeae) or the Ficinia Clade (Cypereae), and we determine whether its unique character combinations (≥10 elongated bristles, reduced sheathing basal leaves, 1–4 spikelets) could be evidence for a new genus or simply mark it as an unusual species within currently recognised genera. In addition, we document the discovery of seven new populations, and we extend its range westward to Lai Châu Province and southward in Lào Cai Province by more than 47 km. Our results demonstrate that Eriophorum scabriculme is best treated in the genus Trichophorum, thus re-circumscribing both genera and their limits with Scirpus s.str. In addition, we emend the description of Trichophorum scabriculme (Beetle) J.R.Starr, Lév.-Bourret & B.A. Ford, provide the first pictures and accurate illustration of the species, and assess its conservation status in Vietnam (VU, Vulnerable). Our study corroborates the fact that in such a diverse and taxonomically difficult family like the sedges, conspicuous characters like highly elongated bristles may be useful for dividing diversity, but they are no guarantee that the groups they mark are natural.
Keywords: Vietnam; Trichophorum; Eriophorum; Conservation; Embryology; Phylogeny; Scirpus; Morphology; Cyperaceae; cpDNA